2020
DOI: 10.1063/1.5126327
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of α-Fe/Nd2Fe14B magnetic core/shell nanocomposites with enhanced energy product for high temperature permanent magnet applications

Abstract: This is a repository copy of Atomistic simulations of α-Fe /Nd2Fe14B magnetic core/shell nanocomposites with enhanced energy product for high temperature permanent magnet applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…The (BH) max values obtained for the considered compounds are found to be in comparison to the experimentally and theoretically obtained values of Nd 2 Fe 14 B [61,62] . The highest μ 0 H c that may be attained experimentally is determined by the μ 0 H a , and it has been demonstrated that the maximum μ 0 H c can be about one-quarter of the μ 0 H a value, and such discrepancy between experiment and theory maybe attributed to 'Brown paradox' [63].…”
Section: Resultssupporting
confidence: 60%
“…The (BH) max values obtained for the considered compounds are found to be in comparison to the experimentally and theoretically obtained values of Nd 2 Fe 14 B [61,62] . The highest μ 0 H c that may be attained experimentally is determined by the μ 0 H a , and it has been demonstrated that the maximum μ 0 H c can be about one-quarter of the μ 0 H a value, and such discrepancy between experiment and theory maybe attributed to 'Brown paradox' [63].…”
Section: Resultssupporting
confidence: 60%
“…The models are composed of soft and the hard mage exchange interactions among theses, respectively depicted in Fig. 21(a Westmoreland, et al [92] studied the effect of the soft magnet  -Fe by MC simulation and the SLLG equation using an atomistic Hamiltonian with thermal fluctuation. They used a simplified Hamiltonian that gives critical temperatures correctly, although the spin-reorientation transition is not realized.…”
Section: Effect Of Soft-magnet Grain Boundary On Coercivitymentioning
confidence: 99%
“…The Nd Fe B magnet consists of hard-magnet (Nd Fe B) grains, each of which is covered by a grain boundary material [ 24 , 51 , 54 , 90 ]. Thus, it is important to study how boundary phases affect the coercivity of the grains studied in the previous section.…”
Section: Effect Of Grain Boundarymentioning
confidence: 99%
“…Micromagnetics continuum modellings for permanent magnets have been applied in analyses of magnetic properties of the Nd magnet [21]. However, to study the microscopic details, recently developed atomistic models are indispensable [16,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Unlike the continuum modellings, the lattice structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1) is introduced with * Electronic address: nishino.masamichi@nims.go.jp microscopic magnetic parameters and the temperature effect can be treated properly in the atomistic modellings. By using the atomistic models, quantitative properties of the Nd magnet have been intensively investigated [16,[22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%